Aurora 3 : 1989-90. - Ateneum, Art Museum of the Ateneum, Helsinki; Aurora 3, 1989-90 (Helsinki : The Nordic Arts Centre, 1989)
Ahtila, Eija-Liisa ; Andersson, Lars ; Billgren, Ernst ; Björnsdottir, Svava ; Book, Ingrid ; Edefalk, Cecilia ; Formo, Per ; Gudni, Georg ; Hardarson, Kristinn G. ; Juutilainen, Kari ; Kanervo, Marja ; Kjerrman, Pontus ; Ngoma, Germain ; Olsen, Martin R. ; Paalgard, Lars ; Pipping, Caroline ; Polack, Lillian ; Ragnarsdottir, Gudrun Hronn ; Ruge, Ane Mette ; Svenungsson, Jan
Aurora 3, 1989-90, The Nordic Arts Centre, (Pohjoismainen Taidekeskus / Nordiskt Konstcentrum), Helsinki, 27.8. - 1.10.1989 ; Ateneum, Art Museum of the Ateneum, Helsinki, 27.8. - 24.9.1989
boek